Channel catfish use higher coordination to capture prey than to swallow. Issue 1901 (17th April 2019) - Olsen, Aaron M.; Hernández, L. Patricia; Camp, Ariel L.; Brainerd, Elizabeth L.
Abstract : When animals move they must coordinate motion among multiple parts of the musculoskeletal system. Different behaviours exhibit different patterns of coordination, however, it remains unclear what general principles determine the coordination pattern for a particular behaviour. One hypothesis is that speed determines coordination patterns as a result of differences in voluntary versus involuntary control. An alternative hypothesis is that the nature of the behavioural task determines patterns of coordination. Suction-feeding fishes have highly kinetic skulls and must coordinate the motions of over a dozen skeletal elements to draw fluid and prey into the mouth. We used a dataset of intracranial motions at five cranial joints in channel catfish ( Ictalurus punctatus ), collected using X-ray reconstruction of moving morphology, to test whether speed or task best explained patterns of coordination. We found that motions were significantly more coordinated (by 20–29%) during prey capture than during prey transport, supporting the hypothesis that the nature of the task determines coordination patterns. We found no significant difference in coordination between low- and high-speed motions. We speculate that capture is more coordinated to create a single fluid flow into the mouth while transport is less coordinated so that the cranial elements can independently generate multiple flows to reposition prey. Our results demonstrate the benefits of both higher and lower coordination in animal behaviours and the potential of motion analysis to elucidate motor tasks.